High resolution radiosonde measurements from station Ny-Ålesund (2025-07) - Marion Maturilli (PANGAEA, 2025)
At AWIPEV research base in Ny-Ålesund, Svalbard, regular radiosonde launches are operated once per day. The launch frequency may increase to 6-hourly soundings during specific campaign periods. The Vaisala RS41-SGP radiosondes provide data of pressure, temperature, relative humidity, wind speed and wind direction from ground to about 30 km height. The given data set contains vertical profiles with 1-second time resolution data as obtained by the manufacturer extquotesingles data processing, quality controlled for appropriate physical ranges.
In: Maturilli, M (2020): High resolution radiosonde measurements from station Ny-Ålesund (2017-04 et seq) [dataset publication series]. Alfred Wegener Institute - Research Unit Potsdam, PANGAEA, https://doi.org/10.1594/PANGAEA.914973